Property of Melatonin of Acting as an Antihypertensive Agent to Antagonize Nocturnal High Blood Pressure: A Meta-Analysis - Vecchis, Renato De; Paccone, Andrea; Maio, Marco Di (International Journal of Statistics in Medical Research, 2019)
Therapy of hypertension persisting in the course of nocturnal sleep has yielded rather disappointing results . Therefore, the research has focused on drugs such as melatonin acting in such a way so as to counteract the lack of fall in blood pressure during night time sleep. A meta-analysis has been planned by gathering only randomized controlled trials( RCTs), where melatonin was administered as a single dose at bedtime and compared with placebo. The efficacy was the "night time variation in systolic blood pressure" and the "night time variation in diastolic blood pressure". Safety endpoint was the possible occurrence of serious adverse events. Seven studies with 221 participants were pooled in the meta-analysis. Melatonin use was a predictor of significant decrease in nocturnal systolic blood pressure[SBP]( difference in means[MD]= -5.74 mm Hg; 95% CI: -6.07 to- 5.41 mm Hg; p<0.00001).This change was generated by the very steep decrease in nocturnal SBP detected in patients treated with controlled-release(CR) melatonin ( MD=-8.42 mm Hg; 95% CI: -8.82 to- 8.02 mm Hg; p<0.00001); whereas the mean change in nocturnal SBP, found in patients taking fast -release (FR)melatonin, was nonsignificant (MD=-0.06 mm Hg; 95% CI: -0.64 to 0.52 mm Hg; p=0.84). Likewise, use of melatonin was associated with a fall in DBP( MD= -0.60 mm Hg; 95% CI=-1.12 to -0.08 mm Hg), driven by the pressure changes attained by the CR melatonin. No major adverse events occurred in the examined trials. Evening administration of CR melatonin has been shown to cause a significant pressure decrease over the nocturnal sleep. Thus, the CR melatonin preparations could find a place in the antihypertensive armamentarium for promoting the physiological fall of blood pressure levels during night time sleep.